Extracorporeal membrane oxygenation for near fatal asthma with sudden cardiac arrest. (2nd September 2021) - Lang, Yuheng; Zheng, Yue; Hu, Xiaomin; Xu, Lei; Luo, Zhiqiang; Duan, Dawei; Wu, Peng; Huang, Lei; Gao, Wenqing; Ma, Qunxing; Ning, Meng; Li, Tong
Abstract: Introduction: Near fatal asthma is a life-threatening disorder that requires mechanical ventilation. Near fatal asthma and COPD with sudden cardiac arrest can worsen the outcomes. Previous studies demonstrated that ECMO is a live-saving measure for near fatal asthma that does not respond to traditional treatment. Case study: A patient with near fatal asthma (NFA) and COPD presented with high airway resistance, life-threatening acidemia and severe hypoxemia that failed to respond to conventional therapy. His hospital course was complicated by sudden cardiac arrest when preparing to initiate V-V mode extracorporeal membrane oxygenation (ECMO). The mode immediately changed from V-V to V-A, then to V-AV and finally to V-V mode in order to improve cardiac function and promote recovery of lung function. Results: On the sixth day, ECMO was removed and on the ninth day, he was extubated and transferred to the ward. Finally, the patient was discharged home on the nineteenth day after admission to be followed up in the pulmonary clinic. Conclusions: The early application of ECMO and mode changing plausibly resulted in dramatic improvement in gas exchange and restoration of cardiac function. This case illustrates the critical role of ECMO mode changing as salvage therapy in NFA and COPD with sudden cardiac arrest.